Bentuk Perlindungan Hukum Bagi Konsumen Indonesia yang Dirugikan Akibat Pembelian Produk Palsu dari Pelaku Usaha Luar Negeri Melalui E-Commers - Firdasari, Yessa; Warka, Made (Media Hukum Indonesia (MHI), 2026)
The expansion of electronic commerce has greatly facilitated access for Indonesian consumers to purchase goods offered by foreign business actors. However, this convenience also contributes to the rising circulation of counterfeit items, particularly in the fashion sector, which can result in both material and non-material losses for consumers. This research examines the legal responsibility of foreign sellers and evaluates the effectiveness of consumer protection mechanisms provided under the Consumer Protection Act, the Electronic Information and Transactions Act, and Government Regulation No. 80 of 2019 on Electronic Commerce. Using a normative juridical approach, the study reveals that although these regulations establish a legal foundation for consumers to claim compensation, their implementation remains constrained by several challenges, including difficulties in pursuing foreign businesses, limited jurisdiction, obstacles in proving counterfeit goods, and inadequate oversight by e-commerce platforms. The findings indicate that preventive and repressive legal protections have not yet operated optimally in cross-border online transactions. Strengthening marketplace supervision, requiring foreign business actors to appoint local representatives, enhancing international cooperation, and improving consumer awareness are essential measures to mitigate losses arising from counterfeit products.